Gad8 Protein Is Found in the Nucleus Where It Interacts with the MluI Cell Cycle Box-binding Factor (MBF) Transcriptional Complex to Regulate the Response to DNA Replication Stress - Cohen, Adiel (J Biol Chem, 2016)
The target of rapamycin (TOR) kinase is found at the core of two evolutionarily conserved complexes known as TOR complexes 1 and 2 (TORC1 and TORC2). In fission yeast, TORC2 is dispensable for proliferation under optimal growth conditions but is required for starvation and stress responses. We have previously reported that loss of function of TORC2 renders cells highly sensitive to DNA replication stress; however, the mechanism underlying this sensitivity is unknown. TORC2 has one known direct substrate, the kinase Gad8, which is related to AKT in human cells. Here we show that both TORC2 and its substrate Gad8 are found in the nucleus and are bound to the chromatin. We also demonstrate that Gad8 physically interacts with the MluI cell cycle box-binding factor (MBF) transcription complex that regulates the G(1)/S progression and the response to DNA stress. In mutant cells lacking TORC2 or Gad8, the binding of the MBF complex to its cognate promoters is compromised, and the induction of MBF target genes in response to DNA replication stress is reduced. Consistently, the protein levels of Cdt2 and Cig2, two MBF target genes, are reduced in the absence of TORC2-Gad8 signaling. Taken together, our findings highlight critical functions of TORC2 in the nucleus and suggest a role in surviving DNA replication stress via transcriptional regulation of MBF target genes.